Rational confinement of molybdenum based nanodots in porous carbon for highly reversible lithium storage - Deng, X.; Zhao, B.; Zhong, Y.; Zhu, Y.; Shao, Zongping (R S C Publications, 2016)
A rational synthesis route towards <5 nm transition metal-based nanodots confined in a highly porous carbon matrix is proposed without adding external carbon sources and applied for highly reversible lithium storage. The microstructures and compositions of the as-prepared samples highly depend on the calcination atmosphere.